Oxytocin administration suppresses hypothalamic activation in response to visual food cues - Agatha A. van der Klaauw (Nature Portfolio, 2017)
Abstract The aim of this study was to use functional neuroimaging to investigate whether oxytocin modulates the neural response to visual food cues in brain regions involved in the control of food intake. Twenty-four normal weight volunteers received intranasal oxytocin (24 IU) or placebo in a double-blind, randomized crossover study. Measurements were made forty-five minutes after dosing. On two occasions, functional MRI (fMRI) scans were performed in the fasted state; the blood oxygen level-dependent (BOLD) response to images of high-calorie foods versus low-calorie foods was measured. Given its critical role in eating behaviour, the primary region of interest was the hypothalamus. Secondary analyses examined the parabrachial nuclei and other brain regions involved in food intake and food reward. Intranasal oxytocin administration suppressed hypothalamic activation to images of high-calorie compared to low-calorie food (P = 0.0125). There was also a trend towards suppression of activation in the parabrachial nucleus (P = 0.0683). No effects of intranasal oxytocin were seen in reward circuits or on ad libitum food intake. Further characterization of the effects of oxytocin on neural circuits in the hypothalamus is needed to establish the utility of targeting oxytocin signalling in obesity.